2020
DOI: 10.1002/sres.2753
|View full text |Cite
|
Sign up to set email alerts
|

Identifying behavioural patterns of coupled water‐agriculture systems using system archetypes

Abstract: Managing water and food systems in South Africa is complex given the factors involved in sustainably managing the sector. To ensure sustainable management of water and agricultural systems, equal access to natural resources, and economic equality, the government has implemented policies to regulate the systems and ensure economic growth. However, the unintended consequences of these policies on the sustainability of water and agricultural systems have not been fully understood in South Africa. This paper ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…In particular, archetypes constitute a toolset of templates that can be used to explain common long‐term problematic behaviours from a systemic perspective to assist in identifying interventions that could create a pivotal change in the system's state (Kim, 2000; Senge, 1990). Indicatively, several archetypes have been already employed to describe production patterns in complex agricultural systems (Banson et al, 2016; Nyam et al, 2020). The ultimate goal of ST is to unveil the ‘mental models' level’ (Doyle & Ford, 1998; Senge, 1992), namely, the compilation of values and perceptions (either conscious or unconscious) of both decision‐makers (e.g., farmers) and operators (e.g., land workers) that set up the complex system structure.…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, archetypes constitute a toolset of templates that can be used to explain common long‐term problematic behaviours from a systemic perspective to assist in identifying interventions that could create a pivotal change in the system's state (Kim, 2000; Senge, 1990). Indicatively, several archetypes have been already employed to describe production patterns in complex agricultural systems (Banson et al, 2016; Nyam et al, 2020). The ultimate goal of ST is to unveil the ‘mental models' level’ (Doyle & Ford, 1998; Senge, 1992), namely, the compilation of values and perceptions (either conscious or unconscious) of both decision‐makers (e.g., farmers) and operators (e.g., land workers) that set up the complex system structure.…”
Section: Methodological Approachmentioning
confidence: 99%
“…Notably, the combination of the counterbalancing feedback loops R1 (reinforcing) and B3 (balancing) generates the so‐called ‘limits to growth (or success)’ archetype (Kim, 2000; Meadows, 2009); this system archetype reflects how an initial improvement of performance due to systematic efforts can be decelerated or even declined due to eventual limiting factors (Nyam et al, 2020). Thus, the cumulative effect of continuous growth may induce future problems.…”
Section: Conceptual Model Buildingmentioning
confidence: 99%
“…Studies on agriculture and farming systems (Banson et al 2016, Sharif and Irani 2016, Brzezina et al 2017, Neudert et al 2019, Nyam et al 2022 have applied system archetypes to identify systemic problems and to propose solutions to achieve desired outcomes. System archetypes applied to agriculture and farming systems draw insights into root causes and underlying interacting mechanisms driving unsustainable outcomes (Neudert et al 2019, Nyam et al 2022.…”
Section: Archetype Analysismentioning
confidence: 99%
“…Furthermore, other researchers, including Gohari et al (2017), Masike (2011), Nassery et al (2014), Shahbazbegian and Bagheri (2010) and Soltani and Alizade (2018), applied dynamic systems modelling to study issues related to water such as the effects of drought, water shortage conditions, water resource management, allowable groundwater extraction from the aquifer and sustainable development of water resources. Nyam et al (2020) highlighted four system archetypes that influenced water and agricultural development policies in South Africa. Furthermore, Baiyegunhi and Fraser (2011) and Teimouri (2014) studied the scenario model to reduce the vulnerability of rural households and farmers to poverty and drought, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…investigated several strategies proposed by professionals to restore Urmia Lake. The finding indicated that changing the irrigation system, paying the compensation to farmers and changing the cultivation pattern were considered the most successful strategies.Furthermore, other researchers, includingGohari et al (2017),Masike (2011),Nassery et al (2014),Shahbazbegian and Bagheri (2010) andSoltani and Alizade (2018), applied dynamic systems modelling to study issues related to water such as the effects of drought, water shortage conditions, water resource management, allowable groundwater extraction from the aquifer and sustainable development of water resources Nyam et al (2020). highlighted four system archetypes that influenced water and agricultural development policies in South Africa.…”
mentioning
confidence: 99%